Cotidiano no Trike e territorialidades na cidade - Bernado, Patrícia (2015)
This research began with a proposal to work quotidian in Michel de Certeau perspective. For him, the quotidian can trap and oppress the individual, but is not made up of oppression only because men seek mechanisms to achieve freedom, even if temporary. As deepened the readings on the topic, studies that addressed issues facing the cities of quotidian began to awaken my interest, and a new approach to cities began to be understood. Within this approach, the city is seen as a "social organization", and aspects of urban space cannot be fully understood if we do not take into account the social, political , cultural and symbolic. Even within this view, there are issues related to territoriality. Aspects involving this practice are intertwined with the meanings employees to actions that end up changing the relationship between individuals and the place, and this influences social relations, consequently, the dynamics of the territory. These processes of meaning and ressignification can be conducted by social groups. Such processes are developed in the territories of cities and can be observed through the manifestations of social groups in quotidian. Based on these conceptions I met the Drift Trike, a practice which I will detail in this paper, through the account of my experience in the field. With the intention to understand how does the construction of territoriality in the cities through the daily social practices Drift Trike, my mentor and I, we decided to perform a character with research "ethnographic inspiration". I've been researching the period April to November 2014, participating in this period of the meetings to practice and travel to tournaments. Due to the possibility of an intense and frequent meet, I could identify as occurring everyday social practices of Drift Trike, characterize micro-resistance practices and the ressignification of the streets through the Drift Trike quotidian, and with it, understand the construction of territoriality in space used for practice. At the end of collecting data and based on my perceptions, I understand that the Drift Trike is a leisure activity and a sport, but also consists of a social group, have called as Trike. As a consequence of the dimensions of this social group, I realized that the construction of the territoriality of a city is influenced to a greater or lesser extent, by events and experiences in other cities. This group is made up of various teams from different cities, but between these teams no territorial disputes therefore intruders or strangers are people who do not belong to the Trike from practitioners of other sports to residents nearby. The territoriality process is closely linked to the feeling of ownership, but also to the group identification feeling with the place. When conducting differentiation of shares of the territory in relation to the other seeking link it with the image of the team, that both in relation to other areas within the city, as in relation to other territories of other city playing trike.